Ball recovery patterns as a performance indicator in elite soccer. (March 2014) - Barreira, Daniel; Garganta, Júlio; Guimarães, Pedro; Machado, João; Anguera, Maria T
In soccer, it seems relevant to understand the relationship between the ball recovering and the subsequent success or failure of attacking play. However, few studies have considered the links between the type of ball recovery in different pitch zones, the competition stages and the overall teams success. The present study aims to analyze the attacks ( n = 1619) carried out by the semi-finalist teams in the 2010 FIFA World Cup in order to explore ball recovery patterns as a performance indicator. SoccerEye observational instrument, SoccerEye recording software, Sequential Data Interchange Standard-Generalized Sequential Querier (SDIS-GSEQ) and SPSS analytic software—one-way analysis of variance, two-way analysis of variance and regressions—were applied. Direct ball recovery, in specific by interception and defensive behavior followed by a pass, was the mostly frequent behavior, with the later inducing attacking play efficacy ( p <0.017). Differences were detected between the group and play-off stages with regard to the types of direct ball recoveries. The ball was most often regained in defensive and mid-defensive central zones, evidencing differences to all other pitch zones ( p ≤0.001). Throw-ins were the only type of ball recovery that differentiated the semi-finalists, namely Germany and Spain ( p <0.009). It was found that recovering directly the ball possession in mid-defensive central zones increases attacking efficacy. Consequently, coaches should consider this tactical determinant in order to organize the training process. Specifically, it is fundamental to improve the collective defensive organization protecting central strip zones and simultaneously performing high-pitched pressure to constrain the ball carrier.